The teaching of contemporary history through the carnival of Cadiz: Creative didactic application in a Secondary classroom - Cogollo Pérez, Paloma (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Our study promotes the use of carnival to learn Contemporary History and the use of active methodologies, such as student-focused teaching, which conceives learning as a constructive process. We understand learning as a process and not only as the mere act of receiving information. Active methodologies have become widespread in recent years, promoting the autonomy and participation of students. Likewise, learning must be contextualized in real-world situations and problems, close to the students. This promotes their positive attitude towards learning and boosts their motivation as something essential to foster critical thinking.